Effects of sarcopenia, body mass indices, and sarcopenic obesity on diastolic function and exercise capacity in Koreans - Jung, Mi-Hyang; Ihm, Sang-Hyun; Park, Sang Min; Jung, Hae Ok; Hong, Kyung-Soon; Baek, Sang Hong; Youn, Ho-Joong (Metabolism, clinical and experimental, 2019)
Obesity induces left ventricular diastolic dysfunction and ultimately causes heart failure. Sarcopenic obesity is common in heart failure with preserved ejection fraction (HFpEF). However, the precise mechanism by which sarcopenic obesity is related to HFpEF is poorly understood. We aimed to evaluate the combined effect of sarcopenia (SP) and obesity on left ventricular diastolic function and exercise capacity. This study included 733 healthy subjects who underwent health check-ups in a tertiary hospital in Korea. All participants were categorized into four groups: non-SP/non-obese, SP/non-obese, non-SP/obese, and SP/obese. Comprehensive echocardiography with cardiopulmonary exercise testing was performed. Diastolic dysfunction was defined as an E/e' ratio ≥ 10. Across SP and obesity groups, a gradual decrease in e' velocity and an increase in the E/e' ratio was noted after adjustment for age and sex. Furthermore, a gradual decrease in percent-predicted peak VO2 was observed across the groups. In the multivariate logistic regression analysis, the SP/obese group had the highest risk for diastolic dysfunction (OR 4.27, 95% CI 2.41–7.57), followed by the non-SP/obese group (OR 2.88, 95% CI 1.57–5.29) and the SP/non-obese group (OR 1.90, 95% CI 1.01–3.56) compared with the reference (non-SP/non-obese) group even after controlling for various confounders. Sarcopenic obesity was associated with impaired diastolic function and decreased exercise capacity, suggesting a possible mechanism by which sarcopenic obesity contributes to the development of HFpEF. •Sarcopenic obesity was associated with impaired diastolic function and exercise intolerance.•The present study highlighted the importance of measuring body composition in the reclassification of obese populations.•Our data implied the possibility of both obesity and sarcopenia as targets for the prevention of HFpEF.